Exports and Productivity : The Role of Imported Inputs and Investment in R&D - Manghnani, Ruchita (World Bank, Washington, DC, 2020)
The empirical evidence on within firm productivity improvements from exports has largely been understated because the measures of revenue productivity used do not account for pricing heterogeneity across firms. Using a panel of Indian firms, the analysis in this paper controls for firm variation in prices and uses proxy methods to retrieve measures of productivity that reflect physical productivity. Within-firm productivity changes from export entry are computed using a difference-in-differences matching estimator. The findings show that, over a six-year period, the difference in productivity growth between export entrants and their non-exporter counterparts is about 11 percentage points. Thus, productivity improvements from selling in international markets have largely been understated in the export-productivity empirical literature. This difference in productivity growth is decomposed into two channels. About 15 percent of the difference in productivity growth is explained by higher imports of intermediate inputs, and about 85 percent is explained by investment in research and development. The evidence suggests that investment in research and development is an important source of within-firm productivity gains even in developing countries.